PERFORMANCE OF MEMBRANES CROSSLINKED WITH GLUTARALDEHYDE IN PERVAPORATION SEPARATION - S.H. Tan; A.L. Ahmad; M.G. Mohd. Nawawi; H. Hassan (Universitas Gadjah Mada, 2002)
Chitosan membranes crosslinked with glutaraldehyde (GA) were prepared through a solution method, where the dry homogeneous chitosan membranes were immersed into the reaction solutions containing 1.25 x 10-3 wt. % of glutaraldehyde (GA). The extent of the crosslinking was controlled by varying the crosslinking time from 1 to 5 minutes. The prepared crosslinked membranes were used for pervaporation dehydration of isopropanol-water mixtures. The influence of feed composition on the separation characteristics has been investigated. The 2-minute-crosslinked-membrane yields the highest water concentrations in the permeate with moderate flux at 50 wt. % of isopropanol in the feed solution. The overall pervaporation results for the homogeneous and crosslinked membranes are compared in term of pervaporation separation index (PSI). The crosslinked membranes showed higher pervaporation separation index (PSI) than that of uncrosslinked membranes especially for isopropanol in feed solution below 78 wt. %.